2016
DOI: 10.1017/s000711451600132x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and relative validity of a FFQ to estimate the intake of fatty acids

Abstract: We investigated the validity and reproducibility of the FFQ used in the Dutch European Investigation of Cancer and Nutrition cohort, in order to rank subjects according to intakes of fatty acid classes and individual fatty acids. In total, 121 men and women (23-72 years) filled out three FFQ at 6-month intervals between 1991 and 1992. As a reference method, they filled out twelve monthly 24-h dietary recalls (24HDR) during the same year. Intra-class correlation coefficients for the FFQ showed moderate to good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(94 reference statements)
0
9
0
1
Order By: Relevance
“…The FFQ was validated against 12 24-h recalls between both genders before the start of the study [ 18 ]. Spearman’s correlation coefficients for intake of total SFA and individual SFA ranged from 0.53 to 0.71 in men and from 0.30 to 0.66 in women [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFQ was validated against 12 24-h recalls between both genders before the start of the study [ 18 ]. Spearman’s correlation coefficients for intake of total SFA and individual SFA ranged from 0.53 to 0.71 in men and from 0.30 to 0.66 in women [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intake of individual SFA was calculated from the Dutch food composition table 1998 (digital update). Using the analogy of a previous research [ 19 ], seven independent predefined food groups were identified which together contribute > 82% of the mean total SFA intake in the study population: butter, cheese, milk and milk products, meat, cakes, snacks and fats. The group of fats was separated into two subgroups based on their SFA content: hard and solid fats (including margarines and fats in wrappers and solid frying fats, all of which contained ≥ 20 g SFA/100 g of the product) and soft and liquid fats (including soft margarines, vegetable oils, liquid fats, and frying oils, all of which contained < 20 g SFA/100 g of the product).…”
Section: Methodsmentioning
confidence: 99%
“…Validity of the FFQ was assessed by comparison with 12 24 h recalls among 121 men and women. In men, Spearman’s rank correlation coefficients showed good validity for milk and milk products (0.69), moderate validity for cheese (0.56), fair validity for meat (0.39) [22] and good to moderate validity for the intake of FA (SFA 0.55, MUFA 0.66, PUFA 0.52) [24]. In women, the validity was good for milk and milk products (0.77), fair for cheese (0.32), moderate for meat (0.59) [22] and moderate to fair for the intake of FA (SFA 0.50, MUFA 0.58, PUFA 0.22) [24].…”
Section: Methodsmentioning
confidence: 99%
“…Estimated intake of energy, macronutrients, and micronutrients from FFQ was higher and substantial than the reference method (24hR), which has been usually applied in studies of development and validation of FFQ in adult female populations in several countries, including Mexico [10,18,[21][22][23][24]26].…”
Section: Discussionmentioning
confidence: 99%